Pelatihan Memaksimalkan Potensi ChatGPT: Teknik PROMPT Engineering Dalam Mendukung Kegiatan Organisasi Bagi Pemuda JPRMI Jakarta - Sita Anggraeni; Syaifur Rahmatullah; Achmad Rifai; Tyas Setiyorini (CV. Multi Kreasi Media, 2024)
In The rapid and significant development of artificial intelligence (AI) has formed a new habit, people are now using AI to facilitate daily activities. Concerns arise because the significant development of AI is not accompanied by adequate knowledge about the use of AI. To overcome the problems that arise, it is important for people to understand what AI does. The rapid development of technology and information, the use of technology-based tools such as ChatGPT (Chat Generative Pre-trained Transformer) can be a potential in supporting activities in an Organisation. One of the prominent AI technologies is ChatGPT, a language model capable of understanding and generating text in a very human-like manner. The rapid development of technology and information, the utilisation of technology-based tools such as ChatGPT (Chat Generative Pre-trained Transformer). To maximise the potential of ChatGPT, an in-depth understanding of prompt engineering techniques is required. Prompt Engineering includes the art and science of designing inputs or ‘prompts’ given to AI models such as ChatGPT to produce desired outputs. With this technique, users can direct the model to provide answers that are more relevant, informative, and suited to specific needs. Jaringan Pemuda & Remaja Masjid Indonesia (JPRMI) has many positive activities in the organisation but does not yet have knowledge in the use of maximising the potential of ChatGPT, an in-depth understanding of prompt engineering techniques is needed. From this community service, the management of the Indonesian Mosque Youth & Teen Network (JPRMI), can understand the knowledge in using maximising the potential of ChatGPT and an in-depth understanding of prompt engineering techniques, as well as practical steps in making prompt engineering techniques in maximising the potential of ChatGPT in making detailed organisational schedules and planning activities from preparation to making reports in organisational activities.